Nutrition Training Improves Health Workers’ Nutrition Knowledge and Competence to Manage Child Undernutrition: A Systematic Review - Sunguya, Bruno F.; Poudel, Krishna C.; Mlunde, Linda B.; Urassa, David P.; Yasuoka, Junko; Jimba, Masamine (Frontiers in Public Health, 2013)
Background: Medical and nursing education lack adequate practical nutrition training to fit the clinical reality that health workers face in their practices. Such a deficit creates health workers with poor nutrition knowledge and child undernutrition management practices. In-service nutrition training can help to fill this gap. However, no systematic review has examined its collective effectiveness. We thus conducted this study to examine the effectiveness of in-service nutrition training on health workers’ nutrition knowledge, counseling skills, and child undernutrition management practices. Methods: We conducted a literature search on nutrition interventions from PubMed/MEDLINE, CINAHL, EMBASE, ISI Web of Knowledge, and WHO regional databases. The outcome variables were nutrition knowledge, nutrition counseling skills, and undernutrition management practices of health workers. Due to heterogeneity, we conducted only descriptive analyses. Results: Out of 3910 retrieved articles, 25 were selected as eligible for the final analysis. A total of 18 studies evaluated health workers’ nutrition knowledge and showed improvement after training. A total of 12 studies with nutrition counseling as the outcome variable also showed improvement among the trained health workers. Sixteen studies evaluated health workers’ child undernutrition management practices. In all such studies, child undernutrition management practices and competence of health workers improved after the nutrition training intervention. Conclusion: In-service nutrition training improves quality of health workers by rendering them more knowledge and competence to manage nutrition-related conditions, especially child undernutrition. In-service nutrition training interventions can help to fill the gap created by the lack of adequate nutrition training in the existing medical and nursing education system. In this way, steps can be taken towards improving the overall nutritional status of the child population.